2020
DOI: 10.1088/1751-8121/abbc4e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-range interaction on degeneracy of eigenvalues of connection matrix of d-dimensional Ising system

Abstract: We examine connection matrices of Ising systems with long-rang interaction on d-dimensional hypercube lattices of linear dimensions L. We express the eigenvectors of these matrices as the Kronecker products of the eigenvectors for the one-dimensional Ising system. The eigenvalues of the connection matrices are polynomials of the dth degree of the eigenvalues for the one-dimensional system. We show that including of the long-range interaction does not remove the degeneracy of the eigenvalues of the connection m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Let ( , , ) w n m k be a constant of interaction between spins shifted with respect to each other by a distance n along the first axis, by a distance m along the second axis, and by a distance k along the third axis. When the interaction is anisotropic, there are In paper [3], we showed that the ( ) has to be hold. As in the two-dimensional problem, the cases of anisotropic and isotropic interactions differ significantly.…”
Section: Two-dimensional Ising Model 1)mentioning
confidence: 99%
See 3 more Smart Citations
“…Let ( , , ) w n m k be a constant of interaction between spins shifted with respect to each other by a distance n along the first axis, by a distance m along the second axis, and by a distance k along the third axis. When the interaction is anisotropic, there are In paper [3], we showed that the ( ) has to be hold. As in the two-dimensional problem, the cases of anisotropic and isotropic interactions differ significantly.…”
Section: Two-dimensional Ising Model 1)mentioning
confidence: 99%
“…We succeeded to obtain analytical expressions for the eigenvalues of the above-described Ising connection matrices. For the d -dimensional system, the eigenvalues are polynomials of the degree d in the eigenvalues for the one-dimensional system with longrange interaction (see [2,3]). The coefficients of these polynomials are the constants of interaction between spins.…”
Section: =mentioning
confidence: 99%
See 2 more Smart Citations
“…In papers [1][2][3], we calculated eigenvalues of Ising connection matrices defined on d-dimensional hypercube lattices (d = 1, 2, 3 . .…”
Section: Introductionmentioning
confidence: 99%